Comparative Analysis of Temperature External and Internal and Relative Humidity of Electric Egg Incubator - Zulhajji Zulhajji; Muliyati Yantahin (Indonesian Journal of Fundamental Sciences, 2022)
Abstract. This study aimed to determine the ratio of external and internal temperatures and the humidity of the electric egg incubator. This research was designed in three stages. The first stage is the manufacture of an egg incubator, followed by the testing and analysis stage. Based on the data from the measurement and analysis results, it was found that the temperature and humidity in the incubator greatly influenced the quality of the hatching of native chicken eggs. This study used an experimental method and was carried out twice. The first stage of testing and measurement data obtained an average external temperature of 28.5°C, internal 38.2°C, and the humidity of the air in the hatchery room was 56.0%. In contrast, the second stage of testing and measurement obtained data on an average outside temperature of 28.42°C, inside 38,0°C, and humidity in the hatchery room 56.0%. It can be concluded that the ratio of outside and inside temperatures in the incubator must be balanced until the 21st day of hatching. In this case, if the outside temperature rises, the temperature inside the incubator must decrease, with the same relative magnitude. Likewise, the humidity inside must have relatively the same ratio to obtain a perfect hatching process, which is between 50% - 60%.